2D transition metal dichalcogenide nanomaterials: advances, opportunities, and challenges in multi-functional polymer nanocomposites. Issue 3 (5th November 2019) - Ahmadi, Mojtaba; Zabihi, Omid; Jeon, Seokwoo; Yoonessi, Mitra; Dasari, Aravind; Ramakrishna, Seeram; Naebe, Minoo
Abstract : The functionalized TMD nanolayers have the potential to introduce multi-functionalities into polymer matrices, thus leading to the development of high-performance multi-functional composites/nanocomposites. Abstract : This review addresses the current potential of two-dimensional (2D) transition metal dichalcogenide (TMD) nanomaterials for multi-functional polymeric nanocomposites. The properties of TMDs, characterization techniques, the applicability of different synthesis methods along with the surface treatment/modification of TMDs, are comprehensively examined by largely focusing on TMD/polymer nanocomposite preparation. Moreover, a vast range of nanocomposite properties, including mechanical/tribological properties, thermal stability/flame retardancy, and electrical/electronic properties, was investigated. The incorporation of TMDs in both thermoplastic and thermoset matrices can lead to the improvement of the aforementioned properties as reported by many studies in the literature. TMDs can thus possibly be considered not only as a liable reinforcement for polymers to induce multi-functionalities to nanocomposites but also a good hybridizing agent for other types of nano reinforcements. Potential opportunities offered by TMDs in composites/nanocomposites have opened up new horizons in a vast range of applications in different fields, including transportation, electrical/electronic, filtration and biomedical. This review has also compiled publications on the research and developments of TMDs and TMD composites/nanocomposites, from 1970 to the present, with the special focus on molybdenum disulfide (MoS2 ) and tungsten disulfide (WS2 ).